2020
DOI: 10.1002/smll.202000123
|View full text |Cite
|
Sign up to set email alerts
|

Toward High‐Dimensional Single‐Cell Analysis of Graphene Oxide Biological Impact: Tracking on Immune Cells by Single‐Cell Mass Cytometry

Abstract: Graphene, a single layer of hexagonally arranged carbon atoms, is considered the most versatile material available to mankind: the thinnest, the strongest, the lightest, extremely flexible, highly electrically and thermally conductive material, [1,2] a versatile entity for multiple functionalization. Due to its unique combination of superior properties, graphene is the starting platform for new disruptive technologies across a wide range of fields [3,4] Various graphene-based technologies have now transformed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Overall, CyTOF findings confirmed the data obtained by the classic flow cytometry method and allowed to evaluate the impact on the different immune subpopulations, revealing the differences among the four materials that were appreciable only by this high-dimensional single-cell technology. The specific effects of the materials on the distinct immune cell subpopulations could be related to the different uptake of the materials in the different typed of cells, as we previously reported for GO into human PBMC subpopulations, enabling the material detection at CyTOF through the functionalization with indium [38].…”
Section: High-dimensional Single-cell Immune Profiling Of Go With Different Lateral Size and Functionalization On Thirteen Cell Populatiomentioning
confidence: 78%
“…Overall, CyTOF findings confirmed the data obtained by the classic flow cytometry method and allowed to evaluate the impact on the different immune subpopulations, revealing the differences among the four materials that were appreciable only by this high-dimensional single-cell technology. The specific effects of the materials on the distinct immune cell subpopulations could be related to the different uptake of the materials in the different typed of cells, as we previously reported for GO into human PBMC subpopulations, enabling the material detection at CyTOF through the functionalization with indium [38].…”
Section: High-dimensional Single-cell Immune Profiling Of Go With Different Lateral Size and Functionalization On Thirteen Cell Populatiomentioning
confidence: 78%
“…However, the data on the antioxidant activity of GO are contradictory. In 2019 studies, it was shown that GO exhibits low antioxidant activity against H 2 O 2 and OH*, while Qui et al considered about high antioxidant activity of GO (10 μg/ml) to OH*, as well as its ability to neutralize the superoxide anion (at a concentration of about 80 μg / treated / untreated ml) [4,8,13]. Chemical modification of GO (doping with nitrogen, the introduction of various functional groups) significantly increases its antioxidant activity, in this regard, it can be assumed that treatment with PEG affects the neutralization of ROS [6].…”
Section: Resultsmentioning
confidence: 99%
“…20 We previously proposed the use of single-cell mass cytometry to dissect the immunological effects of GBMs on individual cells. 21,22 Recently, we characterized and described a new functionalization of GO with ZnS-doped AgInS2 quantum dots (GO-In) that enables the detection of the material in the indium channel ( 115 In), 23 allowing its high-throughput tracking by single-cell mass cytometry. 21 This new approach revealed the ability of GO-In to interact with human classical monocytes and, unexpectedly, B cells, showing high single-B-cell functional heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Recently, we characterized and described a new functionalization of GO with ZnS-doped AgInS2 quantum dots (GO-In) that enables the detection of the material in the indium channel ( 115 In), 23 allowing its high-throughput tracking by single-cell mass cytometry. 21 This new approach revealed the ability of GO-In to interact with human classical monocytes and, unexpectedly, B cells, showing high single-B-cell functional heterogeneity. 21 The interaction of GBMs with monocytes and monocyte-derived macrophages has been studied by us and others.…”
Section: Introductionmentioning
confidence: 99%